Mini-feed mills as a factor in increasing the volume of feed production in the Russian regions - M. D. Magomedov; E. Yu. Alekseycheva (Вестник университета)
The article studies great importance of livestock products for human body and considers the types of fodder used in animal feeding. The data on ten leading regions in mixed fodder production (Belgorod region, Voronezh region, Chelyabinsk region, Tambov region, Krasnodar region, Leningrad region, Republic of Mordovia, Kursk region, Stavropol region, Penza region) has been given. The historical aspect of mixed fodder production in Russia has been presented and advantage of mini-mills in increasing the volume of mixed fodder production shown. The methodical approach to estimating economic expediency of purchase and use of mixed fodders for animal feeding has been offered and necessity of detailed economic calculations on each concrete variant of purchased mixed fodders use noted. Possible variants of mini-feed mills location have been highlighted considering advanced mini-feed mills of various capacities available in the domestic market.